Discussion (Scottish Historical and Archaeological Internet Reports, 2006)
The most significant result of the excavation is the identification of a possible third defensive ditch outside the fort at Cramond. No evidence for a third ditch has been found in previous excavations, but neither have they provided any grounds for ruling out its existence.